Guidelines for Authors: Cumhuriyet Theology Journal - Yayın Kurulu (Cumhuriyet İlahiyat Dergisi, 2017)
Cumhuriyet Theology Journal reguires writers to use the The Chicago Manual of Style “notes and bibliography” system of referencing.First citation: author(s) first name and last name, title, (if applicable) first and last name of translator or editor, place of publication, publisher, date of publication, page number. Subsequent citations: author’s last name, the short title, and the page number should be indicated in all subsequent citations. Footnote citations should conform to the following examples. References: References should be placed at the end of the text in alphabetical order. If a source has more than one author, the surname and name of the first author should be written, and the other authors should be indicated by et.al. The titles of books and journals should be italicized; article titles and book chapters should be placed in quotation marks.